The impact of sound exposure on heart rate variability in adolescent students - Veterník, Marcel; Tonhajzerová, Ingrid; Míšek, Jakub; Jakušová, Viera; Hudečková, Henrieta; Jakuš, Ján (Physiological research, 2018)
Previous studies of physiological responses to music and noise showed the effect on the autonomic nervous system. The heart rate variability (HRV) has been used to assess the activation of the sympathetic and the parasympathetic nervous systems. The present study was aimed to examine HRV with exposure to four sine-wave pure tones (20 Hz, 50 Hz, 2 kHz and 15 kHz) in an environment where the sound intensity exceeded level 65 dB (A-weighted). The participants (20 adolescent girls) were lying in supine position during exposure protocol divided into 6 periods, the first time with generated sounds and the second time without sounds. In the protocol without sound exposure, the low frequency band of the HRV spectrum was increased compared to the basal state before examination (period_1: 6.05+/-0.29 ms(2) compared to period_5: 6.56+/-0.20 ms(2), p<0.05). The significant increase of root Mean Square of the Successive Differences (rMSSD, period_1: 4.09+/-0.16 s compared to period_6: 4.33+/-0.12 s, p<0.05) and prolongation of R to R peak (RR) interval (period_1: 889+/-30 ms compared to period_5: 973+/-30 ms, p<0.001) were observed in the protocol without sound exposure comparing to the protocol with sound exposure where only bradycardia was observed. Contrary to rather polemical data in literature our pilot study suggests that sounds (under given frequencies) have no impact on the heart rate variability and cardiac autonomic regulation.
Keywords: akustická stimulace; Adolescent; srdeční frekvence; Students; lidé; Female; studenti; Heart Rate; Pilot Projects; Sound; Acoustic Stimulation; mladiství; pilotní projekty; ženské pohlaví; zvuk; Humans